Cocoa and Oil palm putative gene database - Manimekalai, R.; Rakesh, V.H.; Anoop, S.; Thomas, George V. (Journal of Plantation Crops, 2011)
Oil palm and cocoa are important plantation crops and require bioinformatics tools to hasten the research output and aid in crop improvement programmes. The current work was undertaken to assign putative function to available Expressed Sequence Tags (EST’s) of oil palm and cocoa. Annotated EST’s of cocoa and oil palm were developed into searchable database. EST’s of oil palm and cocoa were first retrieved from dbEST. FASTA formatted EST sequences were converted into contigs by running in CAP3. The contigs sequences were run in BLAST tool and their putative functions were predicted based on homology. A database of annotated ESTs was developed using MySQL and PHP programs. In this database, EST’s of cocoa and oil palm, BLAST results and gene information were stored as different tables. The database homepage contains six menus namely ’Home’, ’About database’, ’Tool’, ’Useful links’, ’Site map’ and ’Contact us’. The same page contains annotated gene information for cocoa and oil palm separately. For browsing the annotated ESTs of cocoa and oilpalm, separate text boxes are provided such as ’ESTs’, ’blast results’ and ’gene information’. The text box ’EST’s’ of oil palm has links to six different tables which stores information about six different tissues and cocoa contains seven different tables, which stores information about seven different tissues. The ’gene information’ contains the ’contig number’, ’similarities found in each organism’, ’accession number’, ’structure accession number’ and ’gene function’. The cocoa and oil palm putative gene database - COPGENE is hosted at CPCRI bioinformatics website (www.bioinfcpcri.org).